2022
DOI: 10.1111/jopr.13572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Printing Orientation and Postcuring Time on the Flexural Strength of 3D‐Printed Resins

Abstract: To evaluate the effect of printing orientation combined with different postcuring times on the flexural strength of 3D-printed resins. Materials and methods: A total of 480 rectangular specimens with the dimensions of 64×10×3.3 mm were designed and fabricated from two 3D-printed acrylic resins and one heat-polymerized resin (HP). 3D-printed groups were divided into 3 groups according to printing orientations (0-, 45-, 90-degree); each group was subdivided into 4 groups according to postcuring time (30, 60, 90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…In the 45° orientation, the printing layers are in an oblique direction instead of parallel, which may also explain the increased fracture load [ 38 , 40 ]. This finding is in agreement with previous studies [ 38 , 46 , 47 , 48 ]. Turksayar et al [ 38 ] reported the highest fracture strength in the 0° orientation (1094.80 N), which is close to the 30 min groups with all printing orientations.…”
Section: Discussionsupporting
confidence: 94%
“…In the 45° orientation, the printing layers are in an oblique direction instead of parallel, which may also explain the increased fracture load [ 38 , 40 ]. This finding is in agreement with previous studies [ 38 , 46 , 47 , 48 ]. Turksayar et al [ 38 ] reported the highest fracture strength in the 0° orientation (1094.80 N), which is close to the 30 min groups with all printing orientations.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the printing parameters were standardized for all printed resins like 50µm layer thickness and 0-degree printing orientations. 35 In previous studies, 35,36 vertical or horizontal printing orientation were suggested. However, 0 degree was recommended by the manufacturer to make the load applied perpendicular to printing layer orientations as the specimens (full printed teeth no plate or disc specimens) placed on the testing machine with the same printing direction (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While other orientations (45 and 90 degrees) made the load parallel to the printing layer directions which maybe results in layer separations that affect teeth properties. 36 However, this explanation could be considered with cautions as there are no studies that investigated the effect of printing orientations on denture teeth properties.…”
Section: Discussionmentioning
confidence: 99%
“…For heat-polymerized (HP) denture base resin, specimens were prepared using a water bath conventional method as detailed in a previous study [ 29 ]. For 3D-printed resins, the disc specimen was designed virtually and then exported as standard tessellation language (STL) files to 3D printing systems (ASIGA and NextDent printers) [ 30 ]. The study design, including printing parameters and specifications, are listed in detailed in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%